Roux-en-Y gastric bypass pouch outlet reduction using argon plasma coagulation to treat weight regain: a randomized controlled trial with a sham control group - Fittipaldi-Fernandez, Ricardo José; Zotarelli-Filho, Idiberto José; de Santana, Marcelo Falcão; Felicio de Lima, João Henrique; Silva Bastos, Fernando Santos; Barrichello-Junior, Sérgio Alexandre; Teixeira dos Santos, Newton; Guedes, Marcella; Fittipaldi-Fernandez, Aline (Endoscopy International Open, 2023)
Background and study aims A comparative study was conducted to evaluate the efficacy of argon plasma coagulation (APC) therapy in treating post Roux-en-Y gastric bypass (RYGB) weight regain and the incidence of complications related to this procedure, using a sham treatment group as a control.Patients and methods Forty-one patients with a minimum weight regain of 10 kg and a minimum postoperative time of 36 months were randomized into two groups.Results In the APC group (n = 21), the mean initial weight was 100.4 kg and the mean weight regain was 24.94 kg. In the sham group (n = 20), the mean initial weight was 103.65 kg, and the mean weight regain was 25.18 kg. Anastomotic stenosis occurred only after the first APC session. The results for the comparison of APC with the sham group showed a percentage weight regain loss of 63.95 compared to -.65, and weight loss of 15.02 and –0.57), percentage total weight loss of 14.46 and –0.62, excess weight loss of 54.32 % and –2.34 %), and BMI reduction of 5.38 and –0.21, with P < 0.0001 for all the comparisons. In the APC group, there was a significant reduction in HbA1c (5.66 % to 4.96 %) and triglycerides (153.20 mg/dL to 132.20 mg/dL).Conclusions This study indicates that APC outlet pouch reduction outperforms sham treatment in terms of weight loss for patients presenting weight regain after RYGB.